2015
DOI: 10.46538/hlj.12.1.4
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and Beliefs of Teacher Candidates Regarding Heritage Language Maintenance

Abstract: This paper reports on the findings of an investigation that explored teacher candidates’ (TCs) attitudes and beliefs about heritage language (HL) maintenance and variables that may predict their attitudes and beliefs. The participants were 270 TCs in Southwest Florida who completed an on-line survey with Likert-type statements and open-ended questions. Quantitative data was analyzed using factor analysis followed by linear multiple regression analyses. The constructs of TCs’ attitudes and beliefs toward HL mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…This conceptual framework provides visual associations among very different types of bodies of literature to logically link MME to economic benefits, because a direct link seems to be largely lacking from the research literature. More specifically, the extant research literature supports relationships between: cultural diversity and economically-related concepts (Ager and Bruckner, 2013; Ashraf and Galor, 2011; Bove and Elia, 2017); and multilingual and/or multicultural education and cultural sensitivity (Chung, 2018; Micic, 2019; Okoye-Johnson, 2011; Szecsi et al , 2015). …”
Section: Conceptual Framework: Multilingual and Multicultural Educati...mentioning
confidence: 99%
See 2 more Smart Citations
“…This conceptual framework provides visual associations among very different types of bodies of literature to logically link MME to economic benefits, because a direct link seems to be largely lacking from the research literature. More specifically, the extant research literature supports relationships between: cultural diversity and economically-related concepts (Ager and Bruckner, 2013; Ashraf and Galor, 2011; Bove and Elia, 2017); and multilingual and/or multicultural education and cultural sensitivity (Chung, 2018; Micic, 2019; Okoye-Johnson, 2011; Szecsi et al , 2015). …”
Section: Conceptual Framework: Multilingual and Multicultural Educati...mentioning
confidence: 99%
“…multilingual and/or multicultural education and cultural sensitivity (Chung, 2018; Micic, 2019; Okoye-Johnson, 2011; Szecsi et al , 2015).…”
Section: Conceptual Framework: Multilingual and Multicultural Educati...mentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the extent of news exposure has been correlated with stereotypical perceptions of individuals (Dixon 2008): teachers with greater exposure to international news will likely implement more LR teaching. Moreover, research revealed teachers' multilingual background predicted their perceptions of diversity (Flores and Smith 2009;Szecsi, Szilagyi, and Giambo 2015); Szecsi, Szilagyi, and Giambo (2015) found the ability to speak more than one language predicts teacher candidates' positive beliefs about minority students' home languages.…”
Section: Promoting Lr Teaching Practicesmentioning
confidence: 99%
“…Such contact is viewed as an effective means of fostering awareness of cultural differences. Fifth, a small group of studies has viewed multilingual ability as a predictor of teachers' perceptions on cultural diversity (Flores & Smith, 2009;Lee & Oxelson, 2006;Szecsi et al, 2015;Youngs & Youngs, 2001). For instance, a study by Szecsi et al (2015) has shown that the ability to speak more than one language predicts teacher candidates' attitudes about minority students' home languages.…”
Section: Predictors Of Teachers' Cultural Diversity Beliefs and Pract...mentioning
confidence: 99%